MicroRNA-26a–interleukin (IL)-6–IL-17 axis regulates the development of non-alcoholic fatty liver disease in a murine model. (11th November 2016) - He, Q; Li, F; Li, J; Li, R; Zhan, G; Li, G; Du, W; Tan, H
Summary: Non-alcoholic fatty liver disease (NAFLD) is a hepatic presentation of obesity and metabolic syndrome. MicroRNA 26a (Mir-26a) has been reported to play functions in cellular differentiation, cell growth, cell apoptosis and metastasis. A recent paper indicated that Mir-26a regulated insulin sensitivity and metabolism of glucose and lipids. However, the role of Mir-26a in NAFLD still needs to be investigated further. In our current study, vectors encoding pre-Mir-26a (LV-26a) and an empty lentiviral vector (LV-Con) delivered approximately 2 × 10 7 transforming units of recombinant lentivirus were injected into mice through the tail vein. LV-26a-infected mice were protected from glucose dysmetabolism and showed markedly decreased total liver weight, hepatic triglyceride deposition and serum alanine transaminase (ALT) concentration when compared with LV-Con-treated mice. LV-26a-treated mice also exhibited decreased infiltration of immune cells in the liver – something attributed to reduce infiltration of T cell receptor (TCR)-γδ +, granulocyte-differentiation antigen-1 (Gr-1) + cells and CD11b + cells. Next, we found that Mir-26a inhibited the expression of interleukin (IL)−17 and IL-6 in vivo and in vitro . Furthermore, the decreased expression of IL-17 in the liver tissue induced by Mir-26a was abrogated completely by IL-6 overexpression. The decreased total liver weight, hepatic triglyceride deposition and serum ALT concentration induced by Mir-26a was also abrogated completely by IL-6 over-expression. In conclusion, the Mir-26a–IL-6–IL-17 axis regulates the development of NAFLD in a murine model. Graphical Abstract: